Music, Films and Celebrity Environmental Activism to Educate Students to Take Actions (Global Journal of Human-Social Science, 2023)
The main purpo se of this article is to contribute to improving environmental education in school in order to encourage the achievement of 2030 sustainable development goals Agenda This s tudy has an exploratory nature since it involves bibliographical research aimed at highlighting how music films and celebrity activism can be used as educational resources to unlocks the potential for interdisciplinary and multisensory learning in order to evoke emotions raise awareness about environmental issues and inspire students to take action In particular it will be highlighted how teachers can use CLIL approach and thoughtfully selected music videos films and documentaries to facilitates not only the acquisition of linguistic and specific knowledge but also broader skills that are essential in today s interconnected world